Sinopse de leguminosae juss. Do Parque Nacional do Iguaçu, Paraná, Brasil - Rauber, Cristiane Ritter (2019)
The Leguminosae family is one of the most representative in Brazil, with more than 2,800 native species gathered in 222 genera, distributed in all Brazilian phytogeographic domains. It is one of the most representative families in all of them and especially of the Atlantic Forest, where is the Iguaçu National Park (ParNa Iguaçu). This study aims to perform the synopsis of Leguminosae species, with its distribution in different areas of ParNa Iguaçu. ParNa has a total area of about 185,000 hectares, its vegetation is predominantly Semideciduous Forest, in the areas of Foz do Iguaçu and Capanema, and a transition of this with Araucaria forest, in the area of Céu Azul. Monthly collections were carried out on the main trails of ParNa, from April 2018 to May 2019, a survey was also carried out on SpeciesLink, Jabot and Virtual Herbarium Reflora platforms, as well as visits to herbariums, EVB, HCF, MBM, PUC-PR. and UPCB. We found 62 native species of Leguminosae distributed in 40 genera. The most representative genera were Senegalia with seven species, followed by Machaerium, Mimosa and Desmodium with four species each. Among the ParNa species, five species were found only in the FOM area, 50 species only in the FES and eight species are found in the FES and FOM. Two species are endemic to Brazil, Abarema langsdorffii, Albizia polycephala, two endemic to the state of Paraná Mimosa prionopus, Senegalia rafinesquena and two endangered Apuleia leiocarpa, Gleditsia amorphoides. Keys, scientific illustrations and/or photographs with diagnostic characters of the taxa and comments on their geographical distribution are presented.